Solid electrolytic capacitor
The solid electrolytic capacitor design with a porous layer filled with insulating inorganic particles addresses heat and moisture-induced degradation, ensuring stability and extended lifespan.
Patent Information
- Application Number
- CN202290000649.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-07
- Filing Date
- 2022-08-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2032-08-25
AI Technical Summary
Solid electrolytic capacitors are prone to destruction or degradation due to heat sensitivity, moisture absorption, and internal pressure fluctuations, leading to reduced lifespan.
A solid electrolytic capacitor structure is designed with a porous layer filled with insulating inorganic particles, reducing residual bubbles and pressure, and using a conductive polymer with reduced hygroscopicity to minimize thermal degradation and stress.
The structure effectively suppresses destruction and degradation, maintaining capacitor life by reducing thermal stress and internal pressure, while maintaining high electrostatic capacitance.
Smart Images

Figure CN222260815U_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to solid electrolytic capacitors. Background Art
[0002] Conventionally, a solid electrolytic capacitor is a capacitor having a structure including an anode formed of aluminum via a metal and a cathode in which an oxide film is formed by attaching a conductive polymer to the surface of aluminum and an electrode is drawn out from the conductive polymer.
[0003] As a method of extracting the cathode, conductive polymers and carbon can be used to electrically connect the conductive polymers and carbon to a good conductive electrode such as copper. The reason for using conductive polymers and carbon to extract the electrode is that due to the difference in the work function of the materials and the defect rate of the oxide formed on the surface of aluminum, unnecessary conduction and electrical barriers will not be generated in the connection with the good conductive electrode.
[0004] Solid electrolytic capacitors are made by making the surface of aluminum porous, oxidizing the porous aluminum surface to form a dielectric layer composed of oxides, and further arranging a conductive polymer on the surface of the dielectric layer to obtain a large area. The large area provides a solid electrolytic capacitor with a large electrostatic capacitance.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2008-130722 Summary of the invention
[0008] In a solid electrolytic capacitor, there is space (pores) on the surface of the porous aluminum. It is difficult to fill the space, and bubbles are likely to remain in the space. Therefore, if the solid electrolytic capacitor is sealed, the bubbles remaining in the space sometimes expand due to the heat applied from the outside, causing pressure damage. As a result, the solid electrolytic capacitor has a heat-sensitive property. In addition, the conductive polymer used has the property of easily absorbing water, and is easily expanded and contracted due to the humidity of the outside air. Furthermore, there is also the following situation: the absorbed water evaporates and becomes water vapor due to the heat applied from the outside, and the internal pressure of the solid electrolytic capacitor rises, resulting in the destruction of the solid electrolytic capacitor.
[0009] In addition, the conductive polymer has high hygroscopicity and expands and contracts due to moisture absorption and release. Due to this expansion and contraction, internal stress may be generated, and cracks and delamination may occur particularly near the surface of the porous aluminum.
[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a solid electrolytic capacitor having a structure that suppresses destruction or degradation of the solid electrolytic capacitor due to heat applied from the outside and that makes the life of the solid electrolytic capacitor less likely to decrease.
[0011] The solid electrolytic capacitor of the present invention comprises: a valve metal substrate, a porous layer arranged on at least one main surface of the valve metal substrate, a dielectric layer arranged on the surface of the porous layer, and a solid electrolyte layer arranged on the surface of the dielectric layer; the porous layer has a pore portion, and the pore portion is filled with insulating inorganic particles.
[0012] According to the present invention, it is possible to provide a solid electrolytic capacitor having a structure that suppresses destruction or degradation of the solid electrolytic capacitor due to heat applied from the outside and that does not easily reduce the life of the solid electrolytic capacitor. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a cross-sectional view schematically showing the internal structure of a solid electrolytic capacitor.
[0014] Figure 2A This is a process diagram showing the process of manufacturing a solid electrolytic capacitor.
[0015] Figure 2B This is a process diagram showing the process of manufacturing a solid electrolytic capacitor.
[0016] Figure 2C This is a process diagram showing the process of manufacturing a solid electrolytic capacitor.
[0017] Figure 2D This is a process diagram showing the process of manufacturing a solid electrolytic capacitor.
[0018] Figure 2E This is a process diagram showing the process of manufacturing a solid electrolytic capacitor. DETAILED DESCRIPTION
[0019] Hereinafter, the solid electrolytic capacitor of the present invention will be described.
[0020] However, the present invention is not limited to the following configurations, and can be applied with appropriate changes within the scope of the present invention. It should be noted that a configuration in which two or more of the preferred configurations of the present invention described below are combined is also the present invention.
[0021] Figure 1 It is a cross-sectional view schematically showing the internal structure of a solid electrolytic capacitor.
[0022] exist Figure 1 In the solid electrolytic capacitor 10 shown, a porous layer 2 is provided on at least one main surface of a valve metal substrate 1 .
[0023] A dielectric layer 3 is provided on the surface of the porous layer 2 , and a solid electrolyte layer 4 is provided on the surface of the dielectric layer 3 .
[0024] The porous layer 2 has pores 5 , and the pores 5 are filled with insulating inorganic particles 6 .
[0025] Furthermore, solid electrolyte layers 7 (inorganic particle coating layers 7 ) are provided on the surfaces of the insulating inorganic particles 6 , and the insulating inorganic particles become solid electrolyte-coated inorganic particles 8 .
[0026] The valve metal substrate is composed of a valve metal that exhibits a so-called valve action. Examples of the valve metal include simple metals such as aluminum, tantalum, niobium, titanium, and zirconium, or alloys containing these metals. Among these, aluminum or an aluminum alloy is preferred.
[0027] The shape of the valve-acting metal substrate is preferably a flat plate, more preferably a foil.
[0028] The porous layer may be an etched layer formed by etching the valve-acting metal substrate.
[0029] The porous layer has pores, and the average pore diameter of the pores is preferably 10 nm to 600 nm, and more preferably 200 nm to 300 nm.
[0030] The pore size is determined by taking a cross-sectional photograph of the solid electrolytic capacitor and taking the diameter of the pores on the surface of the porous layer. The average pore size of the pores in the cross-sectional photograph is calculated as the average pore size.
[0031] The pore size of the pores is determined by Figure 1 The two arrows W in the cross section shown determine the size of the position.
[0032] In order to increase the electrostatic capacitance, the average pore size is preferably within the above range. If the average pore size is too small, it is not preferred because the conductive polymer and the insulating inorganic particles are less likely to enter the pores.
[0033] The dielectric layer is disposed on the surface of the porous layer and is preferably composed of an oxide film of the valve metal. For example, when aluminum foil is used as the valve metal substrate, an aluminum oxide film can be formed by oxidation in an aqueous solution containing boric acid, phosphoric acid, adipic acid, or their sodium salts, ammonium salts, etc.
[0034] A solid electrolyte layer is provided on the surface of the dielectric layer.
[0035] As materials constituting the solid electrolyte layer, for example, conductive polymers having a skeleton of pyrrole, thiophene, aniline, etc. can be cited. As conductive polymers having a skeleton of thiophene, for example, PEDOT [poly (3, 4-ethylenedioxythiophene)] can be cited, and PEDOT / PSS obtained by compounding with polystyrene sulfonic acid (PSS) as a dopant can also be cited.
[0036] The solid electrolyte layer provided on the surface of the dielectric layer is provided in a film shape, and after the film-shaped solid electrolyte layer is provided, pores remain in the porous layer.
[0037] The pores of the porous layer remaining after the solid electrolyte layer is provided are filled with insulating inorganic particles. The insulating inorganic particles are a concept excluding inorganic particles having conductivity, ie, metal or carbon particles, and preferably metal oxide (metals including silicon) particles can be used.
[0038] As the insulating inorganic particles, at least one kind of fine particles selected from the group consisting of silica and alumina can be appropriately used. In addition, in this specification, the insulating inorganic particles may be simply referred to as inorganic particles.
[0039] By filling the pores of the porous layer remaining after the solid electrolyte layer is provided with insulating inorganic particles, it is possible to reduce the residual bubbles in the pores and prevent pressure collapse due to expansion of the bubbles.
[0040] In addition, the volume ratio of the conductive polymer to be the solid electrolyte layer can be reduced in the pores, thereby preventing thermal degradation and destruction caused by the presence of a large amount of conductive polymer in the pores.
[0041] In addition, it is preferred that a solid electrolyte layer is further provided on the surface of the insulating inorganic particles.
[0042] Figure 1 , solid electrolyte-coated inorganic particles 8 are shown in which a solid electrolyte layer 7 is provided on the surface of insulating inorganic particles 6. In this specification, in order to distinguish it from the solid electrolyte layer provided on the surface of the dielectric layer, the solid electrolyte layer provided on the surface of the insulating inorganic particles is also referred to as an inorganic particle coating layer.
[0043] If described in more detail Figure 1 In the illustrated embodiment, it can be said that the pores 5 are filled with the solid electrolyte-coated inorganic particles 8 so as to be in contact with the solid electrolyte layer 4 provided on the surface of the dielectric layer 3 .
[0044] Since the inorganic particles such as silicon dioxide filled in the pores are insulating inorganic particles, if the inorganic particles are filled in the pores, the resistance of the conductive part from the anode to the cathode becomes higher. If the resistance of this part is high, the series resistance component enters the capacitor, and the loss as the capacitor becomes larger. Therefore, it is necessary to make the material filled in the pores low-resistance.
[0045] The conductive polymer used in the formation of the solid electrolyte layer is a resin with high conductivity, but in order to exert high conductivity, it is preferably appropriately dispersed with conductive polymer particles. If the particles of the conductive polymer agglomerate or agglomerate, the conductivity is hindered. Therefore, the primary particles of the conductive polymer are attached to the surface of the insulating inorganic particles, and the insulating inorganic particles are coated with the conductive polymer. Then, the solid electrolyte coated inorganic particles formed by the conductive polymer coated insulating inorganic particles are filled in the pores of the porous layer.
[0046] This can reduce the resistance of the material filling the pores to reduce the loss as a capacitor, and reduce the volume ratio of the conductive polymer filling the pores to prevent thermal degradation and destruction caused by the presence of a large amount of conductive polymer in the pores.
[0047] In addition, PEDOT / PSS as a conductive polymer is a material that expands upon hygroscopic absorption, and by reducing the molecular weight of the conductive polymer, the expansion pressure can be reduced.
[0048] As the conductive polymer used for forming the inorganic particle coating layer, the conductive polymers listed as the material constituting the solid electrolyte layer provided on the surface of the dielectric layer can be used.
[0049] The average particle size of the insulating inorganic particles is preferably 10 nm to 100 nm, more preferably 30 nm to 60 nm.
[0050] If the average particle size of the insulating inorganic particles is too small, the insulating inorganic particles are attached to the surface of the conductive polymer and the conductive polymer is coated with the insulating inorganic particles. As a result, sometimes the solid electrolyte coated inorganic particles formed by the conductive polymer coating the insulating inorganic particles cannot be obtained. In addition, if the average particle size of the insulating inorganic particles is too large, sometimes the insulating inorganic particles cannot be filled into the pores of the porous layer.
[0051] The average particle size of the insulating inorganic particles is determined as the average value of the particle sizes of a plurality of insulating inorganic particles located in a cross-sectional photograph of a solid electrolytic capacitor.
[0052] In addition, the preferred range of the average particle size of the insulating inorganic particles when the solid electrolyte-coated inorganic particles are used is determined as the average particle size of the insulating inorganic particles without considering the thickness of the inorganic particle coating layer.
[0053] Figure 1 2 shows a state in which a solid electrolyte-coated inorganic particle layer 9 is further present on the porous layer 2 (on the surface of the porous layer but not in the pores). The solid electrolyte-coated inorganic particle layer 9 is a layer of solid electrolyte-coated inorganic particles 8 .
[0054] Furthermore, a conductive layer 13 is provided on the solid electrolyte-coated inorganic particle layer 9 .
[0055] Figure 1 In FIG. 1 , as an example of the conductive layer, an example in which the carbon layer 11 and the metal layer 12 are provided is shown.
[0056] The conductive layer is preferably a carbon layer, a graphene layer, or a metal layer such as a copper layer or a silver layer formed by applying a conductive paste such as a carbon paste, a graphene paste, a copper paste, or a silver paste. In addition, it may be a composite layer in which a metal layer is provided on a carbon layer or a graphene layer, or a mixed layer in which a carbon paste or a graphene paste is mixed with a metal paste.
[0057] It should be noted that when using inorganic particles not coated by a solid electrolyte layer as insulating inorganic particles, since the inorganic particles themselves are insulating, if a layer of insulating inorganic particles is provided between the porous layer and the conductive layer, the resistance value rises. Therefore, it is preferred that a layer of insulating inorganic particles is not provided so that the solid electrolyte layer provided on the surface of the dielectric layer can be electrically connected to the conductive layer.
[0058] Next, an example of a method for producing the solid electrolytic capacitor of the present invention will be described.
[0059] First, the mixed dispersion ink and the conductive resin paste that can be used to produce the solid electrolytic capacitor of the present invention, and the method for producing them are described.
[0060] The mixed dispersion ink is an ink obtained by mixing and dispersing a dispersion of a conductive polymer and a dispersion of insulating inorganic particles.
[0061] The conductive polymer dispersion is preferably a conductive polymer dispersion in water, and the conductive polymer solid content concentration is preferably 2 wt% or less. If the conductive polymer solid content concentration is high, the distance between molecules is close, and aggregation of the conductive polymer may occur.
[0062] The insulating inorganic particles contained in the dispersion of the insulating inorganic particles are preferably subjected to a hydrophilic treatment because PEDOT / PSS, which is preferably used as the conductive polymer, is hydrophilic, and therefore, if the insulating inorganic particles are hydrophilic, the conductive polymer will be appropriately attached to the surface of the insulating inorganic particles.
[0063] The hydrophilic treatment is a treatment for reducing the surface tension, and examples thereof include surface treatment using a coupling agent, UV irradiation treatment, plasma treatment, corona discharge treatment, and other treatments utilizing OH groups introduced by activation in air.
[0064] The dispersion of the insulating inorganic particles is preferably a dispersion dispersed in isopropyl alcohol. Since water and isopropyl alcohol have a high affinity, the dispersion of the conductive polymer dispersed in water and the dispersion of the insulating inorganic particles dispersed in isopropyl alcohol are appropriately mixed.
[0065] When obtaining the mixed dispersion ink, for example, the dispersion of the conductive polymer is stirred while the dispersion of the insulating inorganic particles is added dropwise thereto, so that the insulating inorganic particles are diffused into the conductive polymer. It is preferred that high vibration is applied when stirring the dispersion of the conductive polymer, and as a device for applying high vibration, a disperser using ultrasonic vibration is preferably used. Specifically, a device such as an ultrasonic homogenizer can be used.
[0066] The manner in which the insulating inorganic particles and the conductive polymer adhere to each other differs depending on the size of the insulating inorganic particles.
[0067] When the insulating inorganic particles are too small, especially when the average particle size of the insulating inorganic particles is less than 10 nm, the insulating inorganic particles are attached to the surface of the conductive polymer and the conductive polymer is coated with the insulating inorganic particles. As a result, solid electrolyte-coated inorganic particles formed by the conductive polymer coating the insulating inorganic particles may not be obtained.
[0068] When the size of the insulating inorganic particles is large to a certain extent, especially when the average particle size of the insulating inorganic particles is greater than 30 nm, conductive polymers are attached around the insulating inorganic particles to appropriately obtain solid electrolyte-coated inorganic particles formed by coating the insulating inorganic particles with conductive polymers.
[0069] From the above viewpoints, the insulating inorganic particles are preferably hydrophilically treated particles having an average particle size of 30 nm to 100 nm. In addition, hydrophilically treated silica particles are preferably hydrophilically treated particles having an average particle size of 30 nm to 100 nm.
[0070] Furthermore, the dispersion of the insulating inorganic particles is preferably a dispersion in which silica particles are dispersed in isopropyl alcohol.
[0071] The amount of insulating inorganic particles added is preferably 10 wt % to 100 wt % of inorganic particle solid content mixed with the conductive polymer dispersion. If the above ratio exceeds 100 wt %, the proportion of insulating inorganic particles is too much, the conductivity decreases, and the resistance increases. If the above ratio is less than 10 wt %, the proportion of conductive polymer is too much, and it is difficult to obtain the effect of using insulating inorganic particles.
[0072] The viscosity of the mixed dispersion ink is preferably 2 mPa·s to 10 mPa·s. When the viscosity of the ink is within the above range, it is suitable for forming a solid electrolyte layer by inkjet printing.
[0073] Next, the conductive resin paste will be described.
[0074] The conductive resin paste is obtained by mixing and dispersing the above-mentioned mixed dispersion ink in a water or alcohol dispersion having a high concentration of conductive polymer.
[0075] Preferably, the paste is prepared by mixing a dispersion ink with a high-concentration conductive polymer dispersion in water or alcohol at a ratio of 10 to 50% by weight.
[0076] The conductive polymer is contained in the water or alcohol dispersion of the high-concentration conductive polymer at a solid content concentration of 20% by weight or more. It can be said that the solid content concentration of the conductive polymer is higher than the solid content concentration of the conductive polymer contained in the conductive polymer dispersion used when obtaining the mixed dispersion ink.
[0077] The water or alcohol dispersion of the high-concentration conductive polymer is gel-like and difficult to handle, but by mixing with the mixed dispersion ink, the mixed dispersion ink plays the role of a dispersant and reduces the viscosity of the water or alcohol dispersion of the high-concentration conductive polymer. Therefore, the conductivity of the conductive resin paste is not damaged, and the conductivity is improved. Moreover, it becomes a paste suitable for forming a solid electrolyte layer by screen printing.
[0078] The viscosity of the conductive resin paste is preferably 50 mPa·s to 1000 mPa·s. When the viscosity of the conductive resin paste is within the above range, it is suitable for forming a solid electrolyte layer by screen printing.
[0079] Hereinafter, a process of using a solid electrolytic capacitor using a mixed dispersion ink or a conductive resin paste will be described.
[0080] Figure 2A , Figure 2B , Figure 2C , Figure 2D and Figure 2E This is a process diagram showing the process of manufacturing a solid electrolytic capacitor.
[0081] Figure 2A 2 shows a state in which a porous layer 2 is formed on a main surface of a valve metal substrate 1 , and a dielectric layer 3 is formed on the surface of the porous layer 2 .
[0082] The porous layer may be formed by etching. Alternatively, the dielectric layer may be formed by chemical conversion treatment.
[0083] The chemical conversion treatment is a process of forming an oxide film as a dielectric layer on the surface of a porous layer of a valve metal substrate made of a metal such as aluminum. Adipic acid can be preferably used in the chemical conversion treatment, and the oxide film can be formed by applying a voltage of, for example, 3V.
[0084] The higher the applied voltage, the thicker the oxide film, and the higher the withstand voltage. However, if the oxide film becomes thicker, the electrostatic capacitance becomes smaller. On the other hand, if the voltage is low, the oxide film becomes thinner and the electrostatic capacitance becomes larger. However, if the oxide film becomes too thin, the probability of defects in the oxide film becomes higher, so the applied voltage is preferably 3V or more.
[0085] Figure 2B 2 shows a state where the insulating layer 14 is formed. The insulating layer is formed at a position where the solid electrolyte layer is not formed. By providing the insulating layer, the anode and the cathode are insulated.
[0086] The insulating layer may be formed of a resin. As the resin forming the insulating layer, for example, epoxy resin, phenol resin, polyimide resin, silicone resin, polyamide resin, liquid crystal polymer, etc. are preferably used.
[0087] Figure 2C Schematic diagram showing a state in which a solid electrolyte layer 4 is formed on the surface of a dielectric layer 3 .
[0088] The solid electrolyte layer 4 can be formed by a process of printing a dispersion of a conductive polymer and drying it. The printing and drying of the dispersion of the conductive polymer are preferably repeated a plurality of times.
[0089] The printing of the conductive polymer dispersion can be performed by a method such as sponge transfer, screen printing, spraying, dispenser, inkjet printing, or the like.
[0090] Figure 2D , the insulating inorganic particles (solid electrolyte coated inorganic particles 8) are filled in the pores 5. The filling of the insulating inorganic particles into the pores can be performed by printing the mixed dispersion ink or conductive resin paste described above and drying. The printing and drying are preferably repeated multiple times.
[0091] When using a mixed dispersion ink, it is preferred to print the mixed dispersion ink by inkjet printing. Alternatively, it can also be printed by dripping using a dispenser. This is because the viscosity of the mixed dispersion ink is relatively low.
[0092] When a conductive resin paste is used, it is preferably printed by screen printing. The conductive resin paste has a high viscosity and is thixotropic, and the fluidity of the paste increases during printing, making it easy to penetrate into the pores. Therefore, screen printing is more preferred.
[0093] Figure 2E , a state where a conductive layer 13 composed of a carbon layer 11 and a metal layer 12 is provided is shown.
[0094] The conductive layer can be provided by forming a conductive paste such as a carbon paste or a metal paste mainly composed of silver, copper or nickel on the solid electrolyte layer by sponge transfer, screen printing, spraying, dispenser, inkjet printing or the like.
[0095] Through the above-mentioned steps, the solid electrolytic capacitor of the present invention can be manufactured.
[0096] Example
[0097] Examples of evaluation of the solid electrolytic capacitor of the present invention are shown below, but it should be noted that the present invention is not limited to these examples.
[0098] (Example 1)
[0099] An aqueous dispersion of a conductive polymer (PEDOT / PSS) and a silica sol dispersion (isopropyl alcohol dispersion) were prepared.
[0100] Silica sols having average particle diameters of 20 nm, 45 nm, and 80 nm were prepared from Nissan Chemical Co., Ltd. The solid content concentration of each silica sol was 30% by weight.
[0101] The silica sol having an average particle size of 20 nm had a D10 of 10 nm and a D90 of 30 nm, the silica sol having an average particle size of 45 nm had a D10 of 30 nm and a D90 of 60 nm, and the silica sol having an average particle size of 80 nm had a D10 of 60 nm and a D90 of 100 nm.
[0102] Silica sol having different particle sizes was weighed in terms of solid content at 100 parts by weight of the conductive polymer dispersion. 10 parts by weight, 30 parts by weight, 50 parts by weight, 70 parts by weight, and 100 parts by weight were weighed.
[0103] While the conductive polymer dispersion was stirred and dispersed by an ultrasonic homogenizer at about 300 W, the silica sol dispersion was added dropwise at a rate of 1 g / min.
[0104] The viscosity after dispersion was about 3 mPa·s, which was low. The mixed dispersion ink thus formed was applied to a glass substrate by spin coating at a thickness of 0.2 μm, and the resistivity was measured by a four-terminal method.
[0105] Table 1 shows the measurement results.
[0106] [Table 1]
[0107]
[0108] The coating film (Sample Nos. 2a and 3a) coated with a mixed dispersion ink obtained by dropping a silica sol dispersion having a silica sol with an average particle size of 20 nm into a conductive polymer dispersion had a resistance of 20 MΩ / □ or more and was insulated.
[0109] On the other hand, when silica sol dispersions having average particle sizes of 45 nm and 80 nm were used, the resistivity increased depending on the amount added, but the increase rate was about 1 to 10 times that of the conductive polymer dispersion without the silica sol dispersion.
[0110] From these results, it can be seen that when the particle size of the silica sol contained in the mixed dispersion ink is large to a certain extent (45 nm and 80 nm), the desired conductivity can be maintained.
[0111] It should be noted that this test is a test of applying the mixed dispersion ink and measuring the resistivity, and does not mean that conductivity cannot be ensured when the mixed dispersion ink having a silica sol with an average particle size of 20 nm is used in the production of a solid electrolytic capacitor.
[0112] In addition, a mixed dispersion ink obtained by mixing a dispersion of a conductive polymer with a dispersion of a silica sol has a viscosity of 3 mPa·s or less and is suitable for spin coating and inkjet printing methods.
[0113] Furthermore, the mixed dispersion ink was left to stand at room temperature for 2 weeks to form a coating film, which was then examined using an optical microscope at a magnification of 3000 times. As a result, no aggregation of the mixed dispersion ink occurred.
[0114] (Example 2)
[0115] A high concentration (solid content concentration 20% by weight) conductive polymer (PEDOT / PSS) paste (dispersion medium is water-based) was prepared. 100 g of the paste was placed in a plastic container and placed on a vibrator (60 Hz, amplitude 3 mm). While the viscosity was reduced, the mixed dispersion ink No. 5a, 6a or 8a prepared in Example 1 was added dropwise at a rate of 1 g / min according to the ratio in Table 2. After the addition was completed, the mixture was placed in a high dispersion mixer (Kakuhunter) and stirred for 30 minutes to obtain a conductive resin paste.
[0116] Each conductive resin paste was printed to a thickness of about 30 μm by screen printing, and the resistivity was measured by a four-probe method.
[0117] Table 2 shows the measurement results.
[0118] [Table 2]
[0119]
[0120] High-concentration conductive polymer pastes are severely gelled and have strong thixotropy, and are difficult to mix with the mixed dispersion ink unless placed on a vibrator.
[0121] When only a vibrator was used, the fluidity was insufficient and a gelled state remained, so the mixture was put into a high dispersion mixer (Kakuhunter) to obtain a conductive resin paste.
[0122] In addition, when the ratio of the mixed dispersion ink is less than 30 wt % (sample No. 2b, 3b, 6b, 7b, 10b, 11b), the viscosity increases over time, and the life of the conductive resin paste is short. The conductive resin paste obtained under these conditions needs to be subjected to high dispersion stirring treatment immediately before use.
[0123] (Example 3)
[0124] An aluminum substrate whose surface was processed to form a porous layer was prepared, and a chemical conversion treatment was performed on it to form an oxide film on the surface of the porous layer. Epoxy resin was printed on the aluminum substrate in a pattern of an inner frame of 10 mm□ and an outer frame of 15 mm□, and cured. Thereafter, a dispersion of a conductive polymer (PEDOT / PSS) was printed in the frame of the epoxy resin by inkjet method, and the process of drying at 160°C for 10 minutes was repeated 5 times, and the oxide film (dielectric layer) on the surface of the porous layer was coated with the dispersion of the conductive polymer to form a solid electrolyte layer.
[0125] Thereafter, the mixed dispersion inks No. 4a to 13a prepared in Example 1 were printed by inkjet printing, and the drying step at 180° C. for 10 minutes was repeated several times to make the coating film have a thickness of 5 μm to 20 μm from the surface of the porous layer.
[0126] In addition, a sample using the mixed dispersion ink No. 1a prepared in Example 1 was prepared as a mixed dispersion ink.
[0127] Thereafter, a carbon paste was printed to a thickness of about 20 μm and dried at 180° C. for 30 minutes, and then a copper electrode paste was printed and dried at 200° C. for 30 minutes to obtain a cathode.
[0128] The electrical properties were evaluated by using the back side of the porous layer of the aluminum substrate as the anode and between the aluminum substrate and the copper cathode. The electrostatic capacitance was measured at 1 Vrms and 120 Hz, and the ESR was measured at 1 Vrms and 100 KHz using a commercially available LCR meter. In addition, a voltage of 2 V was applied and the current (leakage current) was measured after 60 seconds.
[0129] Furthermore, a pressure cooker test (high temperature and high humidity test) at 125° C. and 85% RH was repeated three times for 100 hours, and changes in capacitance and ESR before and after the high temperature and high humidity test were examined.
[0130] The measurement results are shown in Table 3.
[0131] [Table 3]
[0132]
[0133] As shown in Table 3, by printing the mixed dispersion ink and filling the pores of the porous layer with insulating inorganic particles, an increase in electrostatic capacitance and a decrease in ESR were observed, and the leakage current was also good.
[0134] A high temperature and high humidity test as an accelerated test was repeated three times. As a result, in the example using the mixed dispersion ink, the fluctuation of ESR was suppressed as well as the electrostatic capacitance.
[0135] When the mixed dispersion ink was not added, delamination was confirmed by cross-section grinding and observation.
[0136] (Example 4)
[0137] An aluminum substrate whose surface was processed to form a porous layer was prepared, and a chemical conversion treatment was performed on it to form an oxide film on the surface of the porous layer. Epoxy resin was printed on the aluminum substrate in a pattern of an inner frame of 10 mm□ and an outer frame of 15 mm□, and then cured. Thereafter, a dispersion of a conductive polymer (PEDOT / PSS) was printed in the frame of the epoxy resin by inkjet method, and the process of drying at 160°C for 10 minutes was repeated 5 times, and the oxide film (dielectric layer) on the surface of the porous layer was coated with the dispersion of the conductive polymer to form a solid electrolyte layer.
[0138] Thereafter, conductive resin pastes No. 2b to 13b prepared in Example 2 were printed using a 10.5 mm□ pattern by screen printing so as to cover the solid electrolyte layer, and a drying step at 180° C. for 10 minutes was repeated twice.
[0139] In addition, a sample using the conductive resin paste No. 1b prepared in Example 2 as a conductive resin paste was prepared.
[0140] Thereafter, a carbon paste was printed to a thickness of about 20 μm and dried at 180° C. for 30 minutes, and then a copper electrode paste was printed and dried at 200° C. for 30 minutes to obtain a cathode.
[0141] By the same method as in Example 3, the electrical characteristics were evaluated.
[0142] Table 4 shows the measurement results.
[0143] [Table 4]
[0144]
[0145] When the conductive resin paste was printed, the electrostatic capacitance increased and the ESR decreased, similarly to the case of printing the mixed dispersion ink of Example 3. Regarding the reduction of ESR, although the ESR became higher than when the mixed dispersion ink was printed, the conductive resin paste was in a paste state, and therefore had the advantage of being able to be screen printed and the number of printings was also small.
[0146] When the conductive resin paste without the mixed dispersion ink was used (sample No. 1b), a significant increase in ESR was observed in the high temperature and high humidity test, but when the other samples (samples Nos. 2b to 13b) were used, a significant increase in ESR was not observed.
[0147] When the sample No. 1b was cross-sectioned and confirmed, delamination was confirmed.
[0148] Explanation of symbols
[0149] 1 Valve action metal substrate
[0150] 2 porous layer
[0151] 3 Dielectric layer
[0152] 4Solid electrolyte layer (solid electrolyte layer on the surface of dielectric layer)
[0153] 5 Pore
[0154] 6Insulating inorganic particles
[0155] 7Solid electrolyte layer (inorganic particle coating layer)
[0156] 8Solid electrolyte coated inorganic particles
[0157] 9Solid electrolyte coated inorganic particle layer
[0158] 10Solid electrolytic capacitors
[0159] 11 Carbon Layer
[0160] 12 metal layers
[0161] 13 Conductive layer
[0162] 14 Insulation layer
Claims
1. A solid electrolytic capacitor, characterized in that: have: Valve action metal base, A porous layer provided on at least one main surface of the valve metal substrate, a dielectric layer disposed on a surface of the porous layer, and A solid electrolyte layer disposed on a surface of the dielectric layer; The porous layer has pores, and the pores are filled with insulating inorganic particles.
2. The solid electrolytic capacitor according to claim 1, wherein: The insulating inorganic particles are at least one selected from the group consisting of silicon dioxide and aluminum oxide.
3. The solid electrolytic capacitor according to claim 1 or 2, wherein: The solid electrolyte layer is further provided on the surface of the insulating inorganic particles.
4. The solid electrolytic capacitor according to claim 1 or 2, wherein: The average pore diameter of the pore portion is 10 nm to 600 nm.
5. The solid electrolytic capacitor according to claim 3, wherein: The average pore diameter of the pore portion is 10 nm to 600 nm.
6. The solid electrolytic capacitor according to claim 1 or 2, wherein: The insulating inorganic particles have an average particle size of 10 nm to 100 nm.
7. The solid electrolytic capacitor according to claim 3, wherein: The insulating inorganic particles have an average particle size of 10 nm to 100 nm.
8. The solid electrolytic capacitor according to claim 4, wherein: The insulating inorganic particles have an average particle size of 10 nm to 100 nm.
9. The solid electrolytic capacitor according to claim 5, wherein: The insulating inorganic particles have an average particle size of 10 nm to 100 nm.
10. The solid electrolytic capacitor according to claim 6, wherein: The average particle size of the insulating inorganic particles is 30 nm to 60 nm.
11. The solid electrolytic capacitor according to any one of claims 7 to 9, wherein: The average particle size of the insulating inorganic particles is 30 nm to 60 nm.